How Do Households Perceive Risks at the Scale of the Environment in Their Own Home?. Issue 2 (April 2013) - Sennes, Vincent; Felonneau, Marie-Line; Gombert-Courvoisier, Sandrine; Ribeyre, Francis
Improving housing performance in ecological terms is a major objective of sustainable development policies. This paper looks at the perception that households have of their environment in their homes, in terms of diagnosis, damages and control. Based on a survey of 107 households, it shows that their environmental concerns only partly reflect current ecological and health risks and that people are finding it difficult to reduce these risks. In order to increase environmental awareness at the level of their homes, the authors highlight the importance of providing support on an individual basis and suggest several courses of action, which should be adapted to the four levels of awareness that were identified by the study.